Latex glove conduit as improvised blood vessel model for microvascular anastomosis training (2020)
Background: In the growing need of microvascular surgery in modern-day plastic surgery, financial burden on surgeon or institution can discourage acquisition of skill particularly in the initial phase of laboratory simulation. This article describes the construction of a cheap, easy-to-make blood vessel model. Materials and method: The model was made using infusion giving set, latex glove, scissors, tape measure and Swan glue CD 308. A cut sheet from the latex glove was rolled twice over two glue- painted segment of the infusion giving set stent. The stents were gently pulled out, turning the sheet into a conduit. The blood vessel model was then allowed to dry. Discussion: The use of latex glove for initial training in microvascular anastomosis has been for long. Previously described productions into a conduit are cumbersome. This model is easy to construct and is useful in an office or dry laboratory setting. Conclusion: The latex glove blood vessel model described in this article is a useful material in the training of budding microsurgeons. Residents in our institution have reported a very good learning experience with its use.